CO-INFECTION WITH COVID-19 AND GENETIC DIVERSITY OF SARS-COV-2 IN CHILDREN - Kamalova, D.; Makibayeva , M.; Amirgazin , A.; Abdrakhmanova , S.; Sytnik , I.; Tuleubaeva , A.; Ramankulov , E; Shevtsov , A. (Eurasian Journal of Applied Biotechnology, 2023)
In the pediatric population, coronavirus infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is more commonly observed in asymptomatic and moderately symptomatic cases. However, when COVID-19 coexists with other infections, it can result in a more severe disease progression. Various subtypes of the SARS-CoV-2 virus are associated with different clinical presentations, with certain subtypes exhibiting a predominance of specific symptoms or manifestations. Clinical manifestations of COVID-19 in children, both during the acute phase of the disease and in the post-COVID-19 period, are not fully understood and different compared to adults. This article presents four clinical cases in which PCR-confirmed COVID-19 was observed in combination with infections caused by viruses such as Ebstein-Barr, varicella, and rotavirus. The severity of the disease in these cases was attributed to symptoms related to intoxication, as well as skin and intestinal syndromes. To understand important genomic signatures of SARS-CoV-2 virus circulating in the area, the genome-wide sequencing was performed for the SARS-CoV-2 samples isolated from nasopharyngeal swabs collected from four patients. Based on the genotyping results, all four samples were found belonging to the SARS-CoV-2 virus Omicron lineage. Three months after the initial testing, follow-up evaluations of the children indicated a higher likelihood of complete recovery. However, some underlying disease manifestations, including anemia and atopic dermatitis, persisted despite the resolution of COVID-19 symptoms.